PRODUKSI TENUN ATBM DENGAN APLIKASI DAN VARIASI PAKAN NON BENANG - Suryo Tri Widodo (Ars: Jurnal Seni Rupa dan Desain, 2008)
ATBM (non mechanical weaving equipment) is very popular in Indonesian weaving. There are various types of woven cloth in Indonesia, such as lurik, warp ikat, double ikat and songket. Indonesian weaving has been developing in many aspects. An innovation on weaving material is significant in the technical aspect of the production process. When ATBM is operated, usually the thread material is used.Nowadays, in addition to the thread material, the non thread ones are also applied.  This article will discuss about the non thread material application on the interior products.Keywords: ATBM, craft textile, non thread weft, weaving material, weaving